2003
DOI: 10.1148/radiol.2261011911
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of New Vertebral Body Fracture after Percutaneous Vertebroplasty in Patients with Osteoporosis

Abstract: A substantial number of patients with osteoporosis develop new fractures after undergoing percutaneous vertebroplasty; two-thirds of these new fractures occur in vertebrae adjacent to those previously treated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
304
4
14

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 519 publications
(334 citation statements)
references
References 12 publications
10
304
4
14
Order By: Relevance
“…No clinical complication observed was linked with cement leakage, even in the foraminal cases. Some authors suggest a relationship between cementation and adjacent vertebral fracture [27], but no cases occurred in our series. One distant osteoporotic vertebral fracture (mid-thoracic) was found in a lumbosacral fusion 8 months after surgery and treated with vertebroplasty.…”
Section: Discussioncontrasting
confidence: 68%
“…No clinical complication observed was linked with cement leakage, even in the foraminal cases. Some authors suggest a relationship between cementation and adjacent vertebral fracture [27], but no cases occurred in our series. One distant osteoporotic vertebral fracture (mid-thoracic) was found in a lumbosacral fusion 8 months after surgery and treated with vertebroplasty.…”
Section: Discussioncontrasting
confidence: 68%
“…Of concern is the increased risk of adjacent vertebral body fractures observed in clinical [4,5] and experimental studies [6][7][8]. Although a recent randomized controlled trial comparing vertebroplasty to conservative treatment [9] found no significant difference in adjacent-level fracture incidence, clinically used poly-methyl-methacrylate (PMMA) cements caused marked changes in load transfer.…”
Section: Introductionmentioning
confidence: 99%
“…La recidiva non controindica peraltro la ripetizione della procedura; nella nostra esperienza, 3 dei 37 pazienti neoplastici trattati sono stati sottoposti con successo ad una nuova procedura in seguito all'estensione della malattia ad altri metameri o a recidiva nello stesso già trattato. Recidive del dolore in pazienti colpiti da crolli osteoporotici possono essere causate dalla frattura di metameri adiacenti: alcuni studi ipotizzano una relazione tra le rinvigorite caratteristiche biomeccaniche della vertebra trattata ed il crollo dei metameri osteopenici adiacenti [22,23]. La naturale tendenza della malattia osteoporotica a produrre fratture vertebrali multiple in metameri adiacenti ported by other authors [12,17] who found vertebroplasty of neoplastic vertebral collapse to be associated with a higher risk of cement leakage, attributing the cause to end-plate erosion by the neoplasm.…”
Section: Fig 3ab Fuga DI Cemento In Una Vena Perivertebrale Immagiunclassified
“…Recurrence is not, however, a contraindication for repeat procedures; in our experience, three out of 37 neoplastic patients were treated successfully with a second procedure following disease extension to other vertebrae or recurrence in a treated vertebra. Pain recurrence in patients with osteoporotic vertebral collapse may be related to the fracture of adjacent vertebrae: some studies have hypothesised a relationship between the strengthened biomechanics of a treated vertebra and the collapse of adjacent osteoporotentro un breve spazio di tempo osservata da altri autori [24], associata alla perdita di sostanza ossea che si verifica nei corpi vertebrali adiacenti a quelli interessati da un crollo [25] ic vertebrae [22,23]. The natural tendency of osteoporosis to produce multiple fractures in adjacent vertebrae within a short time interval noted by other authors [24], associated with the bone loss occurring in vertebrae adjacent to those affected by collapse [25], would tend to minimise the role of the treated vertebra in the pathogenesis of these new fractures.…”
Section: Fig 3ab Fuga DI Cemento In Una Vena Perivertebrale Immagimentioning
confidence: 99%